Bifacial potential of single‐ and double‐sided collecting silicon solar cells. (13th January 2016) - Fertig, Fabian; Wöhrle, Nico; Greulich, Johannes; Krauß, Karin; Lohmüller, Elmar; Meier, Sebastian; Wolf, Andreas; Rein, Stefan
Abstract: Bifacial applications are a promising way to increase the performance of photovoltaic systems. Two silicon solar cell concepts suitable for bifacial operation are the passivated emitter, rear totally diffused (PERT) and the both sides collecting and contacted (BOSCO) cell concepts. This work investigates the bifacial potential of these concepts by means of in‐depth numerical device simulation and experiment with a focus on the impact of varying material quality. It is shown that the PERT cell concept (representing a structure with front‐side emitter only) requires high‐minority‐carrier‐diffusion‐length substrates with L bulk > 3 × W (with cell thickness W ) to exploit its bifacial potential, while the BOSCO cell (representing a structure with double‐sided emitter) can already utilise its bifacial potential on substrates with significantly lower diffusion lengths down to L bulk ≈ 0.5 × W . Experimentally, BOSCO cells with and without activated rear‐side emitter are compared. For rear‐side illumination, the activated rear‐side emitter is measured to increase internal quantum efficiency at wavelengths λ < 850 nm by up to 45%abs (factor of 9) and 30%abs (factor of 2) for cells processed on p ‐type multicrystalline silicon substrates with L bulk ≈ 0.3 × W and L bulk ≈ 2.6 × W, respectively. For PERT cells processed on n ‐type Czochralski‐grown silicon substrates, an according increase in internal quantum efficiency for rear‐side illumination of more than 20%abs (factor of 1.3) is measured when changing from a substrate with L bulk ≈ 3.0 to 10.0 × W . The performed simulations and experiments demonstrate that the BOSCO cell concept is a promising candidate to successfully exploit bifacial gain also on low‐ to medium‐diffusion‐length substrates such as p ‐type multicrystalline silicon, while PERT cells require a high‐diffusion‐length substrate to utilise their bifacial potential. Furthermore, the BOSCO cell concept is shown to be a promising option to achieve highest output power densities, even when using lower quality and therefore possibly more cost‐effective silicon substrates. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work investigates the bifacial potential of the passivated emitter, rear totally diffused (PERT) and the both sides collecting and contacted (BOSCO) cell concepts by means of in‐depth numerical device simulation and experiment. It is shown that the PERT concept (representing structures with front‐side emitter only) requires substrates with bulk diffusion lengths of more than three times the cell thickness to exploit its bifacial potential, while for the BOSCO concept (representing structures with double‐sided emitter) values down to half the cell thickness are sufficient.